The dehumanizing metaphors in the culture of Acehnese in Indonesia - Usman, Jarjani; Yusuf, Yunisrina Qismullah (Indonesian Journal of Applied Linguistics, 2020)
This study investigated dehumanizing metaphors used in the daily life and collective memory of Acehnese people in Indonesia and how male and female persons are presented. The interviews were held with 20 people from six districts in Aceh province, Indonesia. Data were collected from elders aged 60 and above, and Acehnese is spoken as their mother tongue. Since they did not travel much (except for occasional holidays with families and Hajj pilgrimage), they are deemed untainted native speakers of Acehnese. For analysis, grounded by the Conceptual Metaphor Theory, this study found that the metaphorical expressions in the Acehnese culture that dehumanize people mostly use animals' concepts, and the rests are of the inanimate entity, and plants. The negative meanings present human as animals are such as agam buya (crocodile man), kamèng keudèe (goat in the market), manok agam (cock), among others, and the positive ones that present human as plants are boh lam ôn (a leaf-covered fruit) and padé jum (wet rice). They negatively or positively describe a person's behavior where the negative ones are commonly associated with a person's corrupt behavior and the positive ones for good behavior. Most of the dehumanizing metaphors are genderless; only a few are gender-based. Acehnese is a genderless language that has no distinctions of grammatical gender. These metaphors inform the conceptual system or belief of the Acehnese society through language use.